Time series subsidence evaluation using NSBAS InSAR: a case study of twin megacities (Rawalpindi and Islamabad) in Pakistan - Zafar, Waqar Ali; Javed, Farhan; Ahmed, Rizwan; Shah, Muhammad Ali; Ahmad, Mahmood; Khan, Muhammad Younis; Abdullah, Gamil M. S.; Khan, Daud; Najeh, Taoufik; Gamil, Yaser (Frontiers in Earth Science, 2024)
Ground deformation associated with natural and anthropogenic activities can be damaging for infrastructure and can cause enormous economic losses, particularly for developing countries where measuring instruments are absent. Remote sensing techniques like Interferometric Synthetic Aperture Radar (InSAR) can thus play an important role in investigating deformation and mitigating geohazards. Rawalpindi and Islamabad are the twin cities of Pakistan hosting population of around 5.4 million people along with important government and private entities of national and international interest. In this study, we evaluate the rapid paced subsidence in this area using modified Small Baseline Subset technique with Sentinel-1A imagery acquired between 2015 and 2022. Our results show that approximately 50 mm/year subsidence is taking place in older city of Rawalpindi, the most populated zone. We observed that subsidence in the area is controlled by the buried splays of Main Boundary Thrust (MBT), one of the most destructive active faults in the recent past. We suggest that such rapid subsidence most probably is due to aggressive subsurface water extraction. It has been found that in-spite of provision of alternate water supplies by district government, a very alarming number of tubewells are being operated in the area to extract ground water. During the period of 2017 to 2021, field data show that near surface aquifers up to depth of 50-60 m have exhausted and currently most of the tube-wells are extracting water from depth of around 150-160 m. The dropping water level is proportional to the increasing number of tube-wells. Lying at downstream of tributaries originating from Margalla and Murree hills, this area has a good monsoon season and topography supports recharging the aquifers. However, rapid subsidence indicates a deficit between water extraction and recharge, partly due to limitation offered by shale, the low porosity near surface lithology exposed in the area. Other factors amplifying the impacts are fast urbanization, uncontrolled population growth and non-cultivation of the precipitation in the area.